CLAIM MANAGEMENT ANALYSIS OF THE SOCIAL SECURITY AGENCY (BPJS) IN HEALTH WITH BUSINESS PROCESS REENGINEERING APPROACH: A CASE STUDY AT GOVERNMENT HOSPITAL IN INDONESIA - Harnaning, Wuri (Aktualita Manajemen, 2016)
AbstractSocial Security Agency (BPJS) program in health as a follow up of the National Health Insurance (JKN) aims at financing the health of Indonesian society. Therefore, in order to clearly and completely understand health system, health financing subsystems needs to be comprehended as well. But in fact, the hospital unit cost is higher than the BPJS rates lead to the difference in revenue for the government hospital. This research applied depth interview method which is a qualitative method. To reach the research objective, re-engineering of business processes was implemented by using the latest methodology namely revision. From the research result, the researcher found an impact on revenue in one of district general hospitals in Indonesia, especially in the management process of BPJS claim. It was proved from the difference that arised from the difference between the Perwal rates used by general hospital and CBGs INA rates used by BPJS. Â To minimize the difference, clinical pathway is needed by making casemix team and changing the plot of the claims.Â Keywords: plot of BPJS claim, BPJS, business-process re-engineering, clinical pathway, casemix team